Influencing secondary school STUDENTS' conservation behavior intention through an interpretive education program on the malayan tapir. (October 2016) - Lim, E.A; Manohar, M.; Aziz, Azlizam; Zakaria, M.
Highlights: Interpretation was used as a communication tool to influence behavior intention. The pre-test post-test experimental design identifies successful interpretive elements in influencing behavior intention. Thematic and organized interpretive program was effective in influencing students subjective norms and behavior intention. Interpretation made information and experiences relevant to students. Interpretation provoked thinking processes and emotions.